PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN (SAP) DAN PENERAPAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH (SIPKD) TERHADAP KUALITAS LAPORAN KEUANGAN DI PEMERINTAH KOTA DENPASAR - I Kadek Indra Utama (UNHI Press, 2021)
The purpose of this study was to determine the effect of implementing government accounting standards (SAP) and the application of regional financial management information systems (SIPKD) on the quality of financial reports in the government of Denpasar City. The data used in this study use primary and secondary data obtained from respondents who work at the Regional Financial and Asset Management Agency of Denapsar City. The population in this study were 125 people and the sample in this study was 95 people. The method of determining the sample using the proportionate stratified random method. Multiple linear regression analysis technique was used in this study. This study shows the results that the application of government accounting standards has a significant positive effect on the quality of financial reports in Denpasar, which means that the better the application, the better the quality of financial statements presented will be able to provide relevant and reliable financial information. On the other hand, the application of the Regional Financial Management Information System (SIPKD) has no effect on the quality of financial reports in Denpasar City, this is due to technology that has not been used optimally, the lack of OPDs with SIPKD operators who are capable and reliable in applying the system itself.